INTEGRATING READING, WRITING, LISTENING AND SPEAKING SKILLS WITH VISUALS TO ENHANCE LEARNABILITY AND TEACHABILITY - Shahid Nawaz; Sadia Parveen; M. Ammar (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
Language learning is an art and this art is being facilitated by the use of visuals. The integrated approach to language learning and teaching with respect to four basic skills is enhanced and made efficient with the help of visuals. This study is designed to enhance the learnability and teachability of basic language skills with the help of visuals under certain condition. The study is based on quantitative approach and data has been collected through questionnaire which has been analyzed by using statistical tool, SPSS for clear and authentic results. The study has observed that the intended outcomes as reading, writing, listening and speaking skills have been improved with the help of visuals. These outcomes also help to enhance learnability and teachability of learners and teachers respectively.